Consequences of dehesa land use on nutritional status of vegetation in Central-Western Spain - Obrador-Olán, J. J. (…systems. Advances in …, 2004)
A dehesa is a silvoarable system, which results in structure and species simplification of Mediterranean forests. Activities like livestock, forestry, agriculture and, recently, hunting are carried out in these places, in which three main structures are found: trees with native grasses (G), trees with crops (C) and trees with woody understorey (M). In order to find out the effect of dehesa land use on nutritional status, we have measured the nutrient content (N and P) of the vegetation (holm-oak and crop) in three farms located in Central Western Spain, considering in each one the three aforementioned dehesa types. Additionally, the effect of the tree on soil fertility was studied in order to map soil resources around the oak-trees, which will be useful to model the tree-understorey interactions and dehesa functioning. Soil samples (first 20-cm depth) were taken at different distances from the tree (from 2 up to 20 m) in three trees per plot (9 plots: 3 farms x 3 land uses). In all samples, pH, soil organic matter (SOM), cationic exchange capacity (CEC), total N and available P were determined. Foliar nutrient content of holm-oak (N and P) was measured in mature leaves of nine trees per plot. Crop samples were collected at four distances (2, 5, 10 and 15 m) of the trunk of 9 mature trees per plot (only cropped plots). Trees in C plots presented the highest values of leaf-N, which is related to fertiliser application and to organic material incorporation/mineralization. Trees in M plots showed the lowest values of leaf-N, indicating a competitive effect of the matorral. By contrast, highest values of P were found in M plots, indicating a positive interaction between trees and shrubs in P uptake. Differences between C and G plots were not significant. In soils, values of all measured parameters, except pH, diminished according to the distance from the holm-oak, which indicates a marked and positive effect of trees on soil fertility. Regarding the land use, both N and P presented significant differences, being M and C, respectively, which had the highest contents, which does not coincide with the results from leaf nutrient contents. By contrast, N and P values in cereal had a similar behaviour to those of soil, indicating the high dependence of the crop on the nutrients of the first cm of the soil.
Keywords: dehesa management intercropped systems; leaf nutrients; Soil fertility; tree-understorey interactions